O transporte hidroviário urbano de passageiros em Belém e os fatores relevantes para sua implementação - MONTEIRO, Kallyfer Natan Torrinha (2024)
The integration between waterway and road modals is an important feature of cities that have great hydrological potential, due to their ability to improve traffic flow and reduce travel time. In the state of Pará, despite having a vast hydrographic basin, water transportation is little used and does not have integration of the peripheral districts with the economic center of the city. This study investigates how the proposed integration projects between the District of Icoaraci and the center of Belém have not been successful in the past and what factors are relevant for the user to use the waterway modal to the detriment of the road modal, based on a survey carried out to the target public about the waterway modal. The data obtained in the study conclude that users would use the waterway transport if there were integration with different modals for their destinations in the other districts of the capital.